2023
DOI: 10.18063/som.v0i0.816
|View full text |Cite
|
Sign up to set email alerts
|

Oil Spill Detection Using Otical Sensors: A Multi-Temporal Approach

Abstract: Oil pollution is one of the most destructive consequences due to human activities in the marine environment. Oil wastes come from many sources and take decades to be disposed of. Satellite based remote sensing systems can be implemented into a surveillance and monitoring network. In this study, a multi-temporal approach to the oil spill detection problem is investigated. Change Detection (CD) analysis was applied to MODIS/Terra and Aqua and OLI/Landsat 8 images of several reported oil spill events, characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…Remote Sens. 2024, 16, 1792 2 of 15 Moreover, Sentinel-2 has been utilized for identifying oil spills in both marine and freshwater settings [10,11], and several similar studies with other optical sensors are available, too [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Remote Sens. 2024, 16, 1792 2 of 15 Moreover, Sentinel-2 has been utilized for identifying oil spills in both marine and freshwater settings [10,11], and several similar studies with other optical sensors are available, too [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Several investigators have already demonstrated their capabilities for water quality monitoring [28][29][30][31][32][33], particularly in using band 5 at 705 nm, which resolves the secondary reflectance peak related to pigment concentrations [34]. Sentinel-2 was also used to identify oil spills in the sea [35], and several comparable studies are available for other optical sensors [36][37][38]. The visible and infrared reflectance shape features of pure water and oil are relatively similar, and, often, magnitude differences depend heavily on illumination conditions.…”
Section: Introductionmentioning
confidence: 99%